Analisis Kredit Koperasi Karya Cipta Mandiri Dalam Meningkatkan Pendapatan Usaha - Sari Meliana Gulo; Dyah Palupiningtyas; Tri Maryani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to analyze the contribution of credit, level of member satisfaction, and credit services to increasing business income through credit services for members of the Karya Cipta Mandiri Cooperative in Sendangwaru Village, Semarang Regency, Central Java. Using a quantitative approach and SPSS statistical tools, research was conducted on 150 cooperative members who used credit for productive activities. According to the results of descriptive statistical data analysis, member satisfaction levels, credit services, credit contributions, and income increases are all average variables. Classic assumptions such as normality, heteroscedasticity, multicollinearity, and autocorrelation were tested to verify the multiple linear regression model used in the research. According to multiple linear regression analysis, credit contribution and member satisfaction levels have a positive and significant effect on increasing members' business income. In contrast, credit services are not proven to have a significant effect on increasing income. Simultaneous and partial tests show that the three independent variables influence the dependent variable simultaneously.